Pancreas-specific activation of mTOR and loss of p53 induce tumors reminiscent of acinar cell carcinoma - Kong, Bo; Cheng, Tao; Qian, Chengjia; Wu, Weiwei; Steiger, Katja; Cao, Jing; Schlitter, Anna Melissa; Regel, Ivonne; Raulefs, Susanne; Friess, Helmut; Erkan, Mert; Esposito, Irene; et al. (Molecular cancer, 2015)
Pancreatic acinar cell carcinoma (ACC) is a rare tumor entity with an unfavorable prognosis. Recent whole-exome sequencing identified p53 mutations in a subset of human ACC. Activation of the mammalian target of rapamycin (mTOR) pathway is associated with various pancreatic neoplasms. We thus aimed at analyzing whether activation of mTOR with a concomitant loss of p53 may initiate ACC.